Assessment of hydrochemical quality of ground water under some urban areas within Sana’a secretariat - Al- Ariqi, Wadie; Ghaleb, Abduljalil (Eclética Química, 2010)
Groundwater from nine wells of three different districts, located at Sana’a secretariat was analyzed for hydrochemical quality assessment. Measurements of water quality parameters including pH, EC, CO32-, HCO3-,Cl-,NO3-,SO4 2-,Ca2+, Mg2+, Fe3+, K+, and Na+ were carried out . Classification of the groundwater samples according to Cl, SO4 2-, CO32- and HCO3-, hardness (H), total dissolved solids (TDS), base-exchange, and meteoric genesis was demonstrated. Suitability of ground water samples for irrigation and industrial uses according to sodium adsorption ration (SAR), ratio of dissolved sodium (RDS), residual sodium carbonate (RSC) and saturation index (SI) was also investigated. The results of this study showed that almost all ground water samples were of good quality that makes them suitable for drinking and domestic uses. Results also indicated that even though some of the ground water samples were suitable for irrigation purposes, almost all of them were found not be good for industrial uses. Despite all drawbacks of the sewerage system built around Sana’a secretariat at the beginning of the first decade of the third millennium, the results of this study indicate that there is scope of significant improvement in Sana’a secretariat ground water quality.